MORPHOLOGICAL EVALUATION OF PALMARIS LONGUS MUSCLE IN THE POPULATION OF NORTH-WESTERN RAJASTHAN (Asian Journal of Medical Research and Health Sciences, 2026)
Background: The palmarislongus is a superficial forearm flexor with marked variability in its presence and morphology. Its long, accessible tendon is commonly harvested for reconstructive procedures, making population-specific anatomical data clinically relevant. Aims: To determine the prevalence of absence and morphological variants of the palmarislongus, quantify muscle-belly and tendon dimensions, and compare measurements between sides in cadaveric upper limbs from north-western Rajasthan. Materials and Methods:During the cadaveric dissections at the Department of Anatomy, Government Medical College Nagaur, we studied fifty upper-limb (25 right and 25 left). The muscle was categorized as normal, fleshy, reversed, or absent. Length, width, and thickness of the muscle belly and tendon were recorded. Data were summarized as number, percentage, and mean ± standard deviation; group and side-wise comparisons were performed using appropriate tests, with p